2005
DOI: 10.1152/ajpheart.00942.2004
|View full text |Cite
|
Sign up to set email alerts
|

mitoKATP channel activation in the postanoxic developing heart protects E-C coupling via NO-, ROS-, and PKC-dependent pathways

Abstract: Whereas previous studies have shown that opening of the mitochondrial ATP-sensitive K(+) (mitoK(ATP)) channel protects the adult heart against ischemia-reperfusion injury, it remains to be established whether this mechanism also operates in the developing heart. Isolated spontaneously beating hearts from 4-day-old chick embryos were subjected to 30 min of anoxia followed by 60 min of reoxygenation. The chrono-, dromo-, and inotropic disturbances, as well as alterations of the electromechanical delay (EMD), ref… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
37
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 22 publications
(42 citation statements)
references
References 48 publications
5
37
0
Order By: Relevance
“…29 Recently, we have reported no modification in the respiratory rate of mitochondria from chicken skeletal muscle as a result of treatment with 5-hydroxydecanoate in relation to different respiratory substrates. 32 In this regard, Sarre et al 33 suggested the existence of other factors involved in the ischemic process implied during fatigue, upstream activation of protein kinase C, and inhibiting diazoxide activation of mitoK ATP with chelerythrine. Costa et al 18 and Costa and Garlid 19 suggested that protein kinase G induces the opening of mitoK ATP in a way similar to that achieved by the channel activators, diazoxide and cromakalim, in heart, liver, and brain mitochondria.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…29 Recently, we have reported no modification in the respiratory rate of mitochondria from chicken skeletal muscle as a result of treatment with 5-hydroxydecanoate in relation to different respiratory substrates. 32 In this regard, Sarre et al 33 suggested the existence of other factors involved in the ischemic process implied during fatigue, upstream activation of protein kinase C, and inhibiting diazoxide activation of mitoK ATP with chelerythrine. Costa et al 18 and Costa and Garlid 19 suggested that protein kinase G induces the opening of mitoK ATP in a way similar to that achieved by the channel activators, diazoxide and cromakalim, in heart, liver, and brain mitochondria.…”
Section: Discussionmentioning
confidence: 99%
“…In our case, we observed an increase in the presence of both drugs. It is possible that mitoK ATP could be activated by mitochondrial nitric oxide synthase, 33 a place the nitric oxide synthase inhibitor would not have access to.…”
Section: Discussionmentioning
confidence: 99%
“…A small decrease in ATP may also open mitochondrial ATP-dependent potassium (mitoK ATP ) channels, which can increase ROS production under specific conditions [174]. In this regard, inhibitors of mitoK ATP completely inhibited HPV [175], although their specificity for mitoK ATP channels is under debate [176].…”
Section: Ros-independent Triggers Of Hpvmentioning
confidence: 99%
“…For example, the developing embryonic CV system can respond to acute changes in ventricular preload and afterload (10,11) as well as chronic changes in loading conditions (12,13). Acute hypoxia produces a dose-dependent depression in embryonic chick ventricular contractility (14) and the embryonic myocardium displays the ability to survive acute anoxia-reoxygenation with reduced apoptosis versus the mature heart (15,16). Chronic hypoxia late in gestation (d 19) is associated with cardiac contractile dysfunction, ventricular hypertrophy, and aortic intimal hypertrophy (3).…”
mentioning
confidence: 99%